Escrita acadêmica: construção de padrões de recorrência retórica entre resumos e introduções de artigos científicos de graduandos e especialistas. - Guimarães, Kamyla Pradines (2022)
As they enter the university, the student needs to develop writing practices in academic textual genres. Texts produced by undergraduates may not share the same purposes as those produced by experienced authors, and the level of familiarity with textual genres is not the same between these two groups of authors. The novice student needs to deal with specific genres of the university environment, among which the scientific article stands out and, in it, the abstract and introduction as gateways to the full text. It is to be expected that there is a relationship of continuity between the abstract and the introduction of the article, from the point of view of the information included and its distribution in the respective rhetorical movements. Therefore, the objective of this work is to comparatively analyze, in the light of Swalesian genre theory, the distribution of information between the abstract and the introduction of the scientific article of two groups of authors: the novice authors and the specialists of Linguistics. For that, 20 articles will be selected, 10 produced by undergraduates and 10 produced by specialists, the texts will be submitted to the analysis of their rhetorical organization from the CARS model (1990) and the Biasi-Rodrigues model (1998). The results obtained in this research indicate that the sections share similar information, but, in some cases, of a different cognitive nature. We also observed that summary and introduction sections produced by undergraduates do not fully realize the rhetorical units expected for them. And, as a possible remedy, it was observed, however, that the sections rarely assume the role of exchanging information that was omitted in one of them. And, regarding the sections produced by specialists, we noticed that most perform the expected rhetorical units. Therefore, the distribution of information between the sections was much more in the sense of reiterating something previously said or expanding the detail in the reporting of information. In short, the exchange of information was more recurrent in undergraduate articles.